The THE OF EFFECTIVENESS THE EDMODO APPLICATION ON STUDENT LEARNING OUTCOMES IN THE MATERIAL OF ROOFING MAINTENANCE AND REPAIR PROCEDURES AT SMK NEGERI 1 PALANGKA RAYA T.A 2021/2022 - Pasaribu, Naomi; Pandiangan, Pantur; Wiratno (Jurusan Pendidikan Teknologi Dan Kejuruan, 2022)
This study aims to determine the application of Edmodo learning media to student learning outcomes on the material for maintenance and repair procedures on the roof of the building at SMK Negeri 1 Palangka Raya This study uses a descriptive research with a quantitative approach with a pre-experimental design research method, namely by using a one-group pretest-posttest design form, one class group, in the experimental class applying Edmodo learning media.This study conducted a pretest before using the learning media and posttest after applying the Edmodo learning media, the effectiveness of learning with Edmodo in terms of the number of pretest and posttest learning mastery, cognitive domain mastery, normality test, paired sample T-test, n-gain test, and results student response questionnaire. Judging from the learning outcomes of 47.94 percent and post-test as much as 80.35 percent, there was an increase after being given treatment by 32.41 percent, in terms of the cognitive domain of C2 (Level of Understanding) as many as 82 percent of students answered the questions correctly from 16 questions (C2 ), in terms of the normality test with a normal distribution with a value of Shapiro-walk sig 0.127 > 005, because it is normally distributed, the next calculation to the paired sample t-test h0 is rejected with sig 0.000 < 0.025 then there is a significant difference, in terms of the n-gain test. being at 64.9 percent stated that learning using Edmodo in learning was quite effective with student responses to Edmodo, 94 percent answered strongly agree that Edmodo was used as an Effective LMS. It can be concluded that the application of Edmodo learning media is quite effective because there is an increase in learning outcomes.